Quantitative diagnostics of soft tissue through viscoelastic characterization using time-based instrumented palpation. (January 2015) - Palacio-Torralba, Javier; Hammer, Steven; Good, Daniel W.; Alan McNeill, S.; Stewart, Grant D.; Reuben, Robert L.; Chen, Yuhang
Abstract: Although palpation has been successfully employed for centuries to assess soft tissue quality, it is a subjective test, and is therefore qualitative and depends on the experience of the practitioner. To reproduce what the medical practitioner feels needs more than a simple quasi-static stiffness measurement. This paper assesses the capacity of dynamic mechanical palpation to measure the changes in viscoelastic properties that soft tissue can exhibit under certain pathological conditions. A diagnostic framework is proposed to measure elastic and viscous behaviors simultaneously using a reduced set of viscoelastic parameters, giving a reliable index for quantitative assessment of tissue quality. The approach is illustrated on prostate models reconstructed from prostate MRI scans. The examples show that the change in viscoelastic time constant between healthy and cancerous tissue is a key index for quantitative diagnostics using point probing. The method is not limited to any particular tissue or material and is therefore useful for tissue where defining a unique time constant is not trivial. The proposed framework of quantitative assessment could become a useful tool in clinical diagnostics for soft tissue. Graphical abstract: Highlights: We examine the effectiveness of dynamic instrumented palpation on soft tissue. We study tissue viscoelastic response from dynamic palpation. Quantitative mechanical characterization of prostate cancer as an exemplar. We propose a novel tissue quality index for mechanical diagnostics of soft tissue.